Risk-Based Spatial Planning for Seaweed Aquaculture: A Systematic Review of Methods, Indicators, and Decision Support - Mulyani, Sri (PT FORMOSA CENDEKIA GLOBAL, 2026)
Seaweed aquaculture is a key component of the blue economy but faces significant environmental, climatic, and governance risks that challenge conventional site-suitability planning. This systematic review synthesizes risk-based spatial planning approaches for seaweed aquaculture, focusing on methods, risk indicators, and decision-support tools. Following PRISMA guidelines, it finds that most studies rely on GIS and multi-criteria decision analysis, treating risk implicitly through static environmental proxies. Hazard indicators dominate, while exposure, social-institutional vulnerability, adaptive capacity, and uncertainty analysis are rarely addressed. Decision-support outputs are largely map-based, with limited evidence of policy uptake in marine and coastal planning. The review identifies critical gaps and proposes a research agenda emphasizing integrated risk frameworks, social and governance indicators, explicit uncertainty treatment, and co-designed decision-support systems to enhance policy relevance and climate resilience.